Differences Between Original Intravenous Iron Sucrose and Iron Sucrose Similar Preparations - Toblli, Jorge Eduardo; Cao, Gabriel; Oliveri, Leda; Angerosa, Margarita (Arzneimittelforschung, 2009)
Iron sucrose (Venofer®; reference) has a good safety record and is prescribed in patients with anaemia and chronic kidney disease worldwide, but various iron sucrose similar (ISS) preparations are now utilized in clinical practice. This study evaluates possible differences between iron sucrose and ISS preparations on haemodynamic and oxidative stress markers in normal rats. 60 male and 60 female Sprague Dawley rats were divided into four groups and assigned to receive commercially available ISS test 1, ISS test 2, reference or isotonic saline solution (control). A single i. v. dose of iron (40 mg/kg) or saline (equivalent volume) was administered after 24 h and every 7 days for 4 weeks. Blood samples were collected for biological assessment of haemoglobin (Hb), serum iron and percentage transferrin saturation (TSAT), and urine samples were collected to investigate creatinine clearance and proteinuria. Animals were sacrificed after receiving an i. v. dose on days 1, 7 and 28, and kidney, liver, and heart homogenates were then collected to determine antioxidant enzyme levels. Tissues were processed using Prussian blue and immmunohistochemistry techniques to identify iron deposits, tissue ferritin and pro-inflammatory markers. Systolic blood pressure was significantly reduced in the ISS groups relative to the reference and control groups after 24 h and on days 7, 14 and 21 (p < 0.05). Creatinine clearance was reduced (p < 0.01) and proteinuria marked (p < 0.01) in the ISS groups at 24 h and on days 7 and 28 relative to the reference and control groups which did not differ throughout the study. Liver enzymes were also increased in the ISS groups at 24 h and on days 7 and 28. Both ISS test 1 and ISS test 2 groups presented a significant increase in catalase, thiobarbituric reactive species, Cu, Zn-superoxide dismutase (CuZnSOD) and glutathione peroxidase activity, and a decrease in glutathione levels (p < 0.01) in the liver, heart and kidney at 24 h and on day 7 relative to the reference and control groups. Serum iron and percentage TSAT were elevated in all groups (except control) (p < 0.01) but no differences in Hb concentration were observed between them. Finally, levels of the proinflammatory markers TNF-α and IL6 were significantly elevated in the ISS groups (liver, heart and kidney) compared with the reference and control groups on day 28 (p < 0.01). These findings suggest significant differences between the reference and ISS test 1/ISS test 2 regarding oxidative stress and the inflammatory responses of liver, heart and kidneys in normal rats. A possible explanation for these observations could be the stability of the iron complex.
Keywords: Anaemia; Iron sucrose; Kidney disease, chronic; Oxidative stress; Venofer®